Surgical Training in Pakistan: Time to Move to Specialty Based Practice (Archives of Surgical Research, 2022)
Surgical training in Pakistan has been following the Halstedian model of training. Today the number of hospitals training surgeons in Pakistan has increased. Although commendable this has a huge downside to it. There is a growing perception among the surgical community that we are not moving fast enough to adapt to the rapidly changing needs. College of Physicians and Surgeons of Pakistan (CPSP) has commendably incorporated such elements of the structured training program however quality assurance of these programs at the training institute level has struggled. There is a growing need for improving the quality assurance of residency programs especially at the training institute level.